Effect of various storage media on the physicochemical properties of plasma-treated dental zirconia - Kang, Sung Un; Lee, Da Young; Kim, Yu Kwon; Kim, Seung Joo; Kim, Hee Kyung; Kim, Chul Ho (Scientific Reports, 2024)
This study investigated the effect of various storage media on the physicochemical properties of plasma-treated 3-mol% yttria-stabilized tetragonal zirconia: air, vacuum, deionized water (DIW), and plasma-activated water (PAW). Each group was divided into five subgroups based on storage periods: immediately after NTP irradiation (T0), and after 1 week (T1), 2 weeks (T2), 3 weeks (T3), and 4 weeks (T4). The control group (C) received no treatment. The storage groups were monitored weekly using various analytical techniques, including contact angle measurements, scanning electron microscopy (SEM), focused ion beam (FIB)-SEM, confocal laser scanning microscopy (CLSM), x-ray photoelectron spectroscopy (XPS), and x-ray diffraction (XRD). Our results demonstrate that plasma-treated zirconia surfaces stored in DIW retained or even increased their hydrophilicity due to the formation of hydrogen bonds and preservation of nitrogen functionalities. In contrast, surfaces stored in air exhibited significant hydrophobic recovery. FIB-SEM analysis showed no adverse internal structural changes regardless of storage medium. The roughness of the zirconia surface slightly increased after plasma treatment and was generally retained across all storage groups for 4 weeks, except for the air storage group. This study concludes that storage in DIW effectively preserves the enhanced surface properties of plasma-activated zirconia for up to 4 weeks.
Keywords: Dental Materials; Hydrophobic and Hydrophilic Interactions; Materials Testing; Microscopy, Electron, Scanning; Photoelectron Spectroscopy; Plasma Gases; Surface Properties; Water; X-Ray Diffraction; Yttrium; Zirconium; Hydrophilicity; Hydrophobicity; Non-thermal atmospheric pressure plasma; Surface properties; Water; Zirconia